Controlling the Structural and Electrical Properties of Diacid Oligo(Phenylene Ethynylene) Langmuir–Blodgett Films. Issue 17 (27th February 2013) - Ballesteros , Luz Marina; Martín , Santiago; Cortés , Javier; Marqués‐González, Santiago; Higgins, Simon J.; Nichols, Richard J.; Low, Paul J.; Cea , Pilar
Abstract The preparation, characterization and electrical properties of Langmuir–Blodgett (LB) films composed of a symmetrically substituted oligomeric phenylene ethynylene derivative, namely, 4, 4′‐[1, 4‐phenylenebis(ethyne‐2, 1‐diyl)]dibenzoic acid (OPE2A), are described. Analysis of the surface pressure versus area per molecule isotherms and Brewster angle microscopy reveal that good‐quality Langmuir (L) films can be formed both on pure water and a basic subphase. Monolayer L films were transferred onto solid substrates with a transfer ratio of unity to obtain LB films. Both L and LB films prepared on or from a pure water subphase show a red shift in the UV/Vis spectrum of about 14 nm, in contrast to L and LB films prepared from a basic subphase, which show a hypsochromic shift of 15 nm. This result, together with X‐ray photoelectron spectroscopic and quartz crystal microbalance experiments, conclusively demonstrate formation of one‐layer LB films in which OPE2A molecules are chemisorbed onto gold substrates and consequently COOAu junctions are formed. In LB films prepared on a basic subphase the other terminal acid group is also deprotonated and associates with an Na+ counterion. In contrast, LB films prepared from a pure water subphase preserve the protonated acid group, and lateral H‐bonds with neighbouring molecules give rise to a supramolecular structure. STM‐based conductance studies revealed that films prepared from a basic subphase are more conductive than the analogous films prepared from pure water, and the electrical conductance of the deprotonated films also coincides more closely with single‐molecule conductance measurements. This result was interpreted not only in terms of better electron transmission in COOAu molecular junctions, but also in terms of the presence of lateral H‐bonds in the films formed from pure water, which lead to reduced conductance of the molecular junctions.